Study on the effect of county e-commerce development on rural residents' income growth - Yang, Kun (International Journal of Global Economics and Management, 2024)
Against the background of rural revitalization and the development of county-level e-commerce industry, based on the data of Caoxian County of Heze, Shandong Province from 2017 to 2021, this paper studies the promotion effect of county-level e-commerce industry development on urban and rural residents' income through grey relative correlation analysis. The results show that the impact of the development of county e-commerce industry on the operational income of urban and rural residents is similar, and the impact on the operational income of rural residents is partly greater than that of urban residents, and the effect is not obvious. The influence of the development of county e-commerce industry on the wage income of rural residents is greater than that on the wage income of urban residents.